2012
DOI: 10.1016/j.seizure.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Possession by ‘Jinn’ as a cause of epilepsy (Saraa): A study from Saudi Arabia

Abstract: Jinn possession is still believed to be a cause of epilepsy in Saudi society, even among fairly well-educated people. This finding emphasizes the urgent need for public education campaigns at all levels of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
62
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 17 publications
(25 reference statements)
11
62
5
2
Order By: Relevance
“…There was, however, a selection bias in that study as more than one-third of the participants (39%) had a health-care-related occupation. In studies among university students in Saudi Arabia and Malaysia, the percentages were 81.8% and 86.5%, respectively [18,20]. The Malaysian study, however, did not exclude students studying health-related specialties [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was, however, a selection bias in that study as more than one-third of the participants (39%) had a health-care-related occupation. In studies among university students in Saudi Arabia and Malaysia, the percentages were 81.8% and 86.5%, respectively [18,20]. The Malaysian study, however, did not exclude students studying health-related specialties [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although university graduates represent the most educated segment of modern societies, unfortunately, only few studies worldwide have assessed their knowledge about epilepsy and attitudes toward PWE [15][16][17][18][19][20]. For example, a study from Canada found that students' knowledge about epilepsy was variable but their attitudes were positive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Suudi Arabistan'dan Obeid ve ark. 'nın [8] yaptığı çalışmada epilepsi için ilaç tedavisi dışındaki tedavi seçenekleri telkinle tedavi eden şifacılarca Kur'an'dan okunan dualar, bit- Sudan'da epilepside modern tıp uygulamasını tercih edenler %72.8, modern tıp ile dinsel tedaviyi birlikte uygulayanların oranı %38.8, yalnızca dinsel tedavi uygulama sıklığı %37.4, geleneksel tedavi yöntemlerini uygulama %2.1 ve modern tıbbi tedavi ile geleneksel tedaviyi birlikte uygulama ise %3.9'dur. [9] Winkler ve ark.…”
Section: Discussionunclassified
“…Obeid ve ark. [8] araştırmalarında, Suudi Arabistan'da öğretmen ve üniversi-te öğrencileri arasında yaptıkları çalışma toplumun büyük bir bölümünün, Tekeli ve ark.nın [14] sonucuna benzer şekil-de, epilepsinin "cinler" nedeniyle geliştiğine inandıklarını gösterdi.…”
Section: Discussionunclassified